2008
DOI: 10.1681/asn.2007030392
|View full text |Cite
|
Sign up to set email alerts
|

T-bet Deficiency Attenuates Renal Injury in Experimental Crescentic Glomerulonephritis

Abstract: T-bet is a transcription factor that is essential for T helper (Th)1 lineage commitment and optimal IFN-␥ production by CD4 ϩ T cells. We examined the role of T-bet in the development of experimental crescentic glomerulonephritis, which is induced by Th1-predominant, delayed-type hypersensitivity-like responses directed against a nephritogenic antigen. Anti-glomerular basement membrane (GBM) glomerulonephritis was induced in T-bet Ϫ/Ϫ and wild-type C57BL/6 mice. Compared with wild-type controls, renal injury w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
75
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 45 publications
1
75
0
Order By: Relevance
“…35 On the other hand, abrogation of Th1 signaling by deleting the T-bet gene, a transcription factor for Th1 cells, not only attenuates glomerular crescent formation and accumulation of CD4 ϩ T cells and macrophages, but it also reduces intrarenal expression of RANTES/ CCL5, Mig/CXCL9, and CXCR3. 89 However, injection of Th1 cells in mice increases renal expression of MCP1/ CCL2 and RANTES/CCL5, and causes progressive albuminuria along with crescent formation. 24 Taken together, CCL chemokines participate in activating infiltrating cells related to Th1 immune responses during inflammatory renal injury.…”
Section: Role Of Chemokines In T Cell Infiltration During Kidney Injurymentioning
confidence: 99%
“…35 On the other hand, abrogation of Th1 signaling by deleting the T-bet gene, a transcription factor for Th1 cells, not only attenuates glomerular crescent formation and accumulation of CD4 ϩ T cells and macrophages, but it also reduces intrarenal expression of RANTES/ CCL5, Mig/CXCL9, and CXCR3. 89 However, injection of Th1 cells in mice increases renal expression of MCP1/ CCL2 and RANTES/CCL5, and causes progressive albuminuria along with crescent formation. 24 Taken together, CCL chemokines participate in activating infiltrating cells related to Th1 immune responses during inflammatory renal injury.…”
Section: Role Of Chemokines In T Cell Infiltration During Kidney Injurymentioning
confidence: 99%
“…Realtime PCR was performed on a Rotor Gene RG-3000 (Corbett Research, Mortlake, VIC, Australia) for measurement of T-bet, GATA3, RORgt, IFN-g, IL-4, TNF, IL-6, MAPK phosphatase-1 (MKP-1), glucocorticoidinduced leucine zipper (GILZ), and b-actin using Power SYBR Green PCR Master Mix (Applied Biosystems). Gene-specific oligonucleotide primers were used and synthesized by Invitrogen, as previously described (13,(29)(30)(31). TaqMan-predesigned real-time PCR assays (Applied Biosystems) were used for detection of IL-17A and IL-10.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…9,10 Studies in patients with crescentic GN and experimental models of GN have shown the importance of CD4 + T cell-driven immune responses in this disease group. 9 Today, there is clear evidence that the recruitment of T H 1 11,12 and T H 17 [13][14][15] cells into the inflamed kidney drives renal tissue damage, whereas Tregs suppress overwhelming immune responses. [16][17][18] In this study, we investigated the functional role of chemokine receptors expressed on Tregs in crescentic GN.…”
mentioning
confidence: 99%